2024
DOI: 10.2147/ijn.s444686
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferia parviflora Extracellular Vesicle Loaded with Clarithromycin for the Treatment of Helicobacter pylori Infection

Variya Nemidkanam,
Wijit Banlunara,
Nuntaree Chaichanawongsaroj

Abstract: Kaempferia parviflora extracellular vesicles (KPEVs) have been reported as promising nanovesicles for drug delivery. This study aimed to load clarithromycin (CLA) into KPEVs (KPEVS-CLA) and determine the physical properties, drug-releasing efficiency, gastric cell uptake, anti-H. pylori activities, and anti-inflammatory responses in comparison with free CLA and KPEVs. Methods: The size and surface charge of KPEVs-CLA were evaluated using dynamic light scattering and visualized using a transmission electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…2 In this study, clarithromycin was designed to be loaded into Kaempferia parviflora extracellular vesicles (KPEVs), while the drug delivery and final antibiotic activity of clarithromycin in KPEVs were examined and compared to the free form of clarithromycin in this in vitro study by using adenocarcinoma gastric cells. 1 Since the growing number of cases of antimicrobial resistance (AMR) worldwide are still rapidly reported, the results of this study showed promising novelty as the effort to find a way out of this global health issue. KPEVs were shown and proven to be promising drug delivery vesicles.…”
Section: Dear Editormentioning
confidence: 90%
See 3 more Smart Citations
“…2 In this study, clarithromycin was designed to be loaded into Kaempferia parviflora extracellular vesicles (KPEVs), while the drug delivery and final antibiotic activity of clarithromycin in KPEVs were examined and compared to the free form of clarithromycin in this in vitro study by using adenocarcinoma gastric cells. 1 Since the growing number of cases of antimicrobial resistance (AMR) worldwide are still rapidly reported, the results of this study showed promising novelty as the effort to find a way out of this global health issue. KPEVs were shown and proven to be promising drug delivery vesicles.…”
Section: Dear Editormentioning
confidence: 90%
“…We felt really encouraged to read and review the recent research report reported by Nemidkanam et al since the study provides interesting ideas in providing solutions for antimicrobial resistance in bacterial infection. 1 Clarithromycin is a second-generation broad-spectrum macrolide antibiotic and was generally used in the treatment of Helicobacter pylori infection. 2 In this study, clarithromycin was designed to be loaded into Kaempferia parviflora extracellular vesicles (KPEVs), while the drug delivery and final antibiotic activity of clarithromycin in KPEVs were examined and compared to the free form of clarithromycin in this in vitro study by using adenocarcinoma gastric cells.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations